Passive Immunity for Coronavirus Disease 2019: A Commentary on Therapeutic Aspects Including Convalescent Plasma - Lindholm, Paul F.; Ramsey, Glenn; Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2020)
In the ongoing pandemic of coronavirus disease 2019 (COVID-19), the novel virus SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) is infecting a naïve population. The innate immunity of the infected patient is unable to mount an effective defense, resulting in a severe illness with substantial morbidity and mortality. As most treatment modalities including antivirals and anti-inflammatory agents are mostly ineffective, an immunological approach is needed. The mechanism of innate immunity to this viral illness is not fully understood. Passive immunity becomes an important avenue for the management of these patients. In this article, the immune responses of COVID-19 patients are reviewed. As SARS-CoV-2 has many characteristics in common with two other viruses, SARS-CoV that cause severe acute respiratory syndrome (SARS) and MERS-CoV (Middle East respiratory syndrome coronavirus) that causes Middle East respiratory syndrome (MERS), the experiences learned from the use of passive immunity in treatment can be applied to COVID-19. The immune response includes the appearance of immunoglobulin M followed by immunoglobulin G and neutralizing antibodies. Convalescent plasma obtained from patients recovered from the illness with high titers of neutralizing antibodies was successful in treating many COVID-19 patients. The factors that determine responses as compared with those seen in SARS and MERS are also reviewed. As there are no approved vaccines against all three viruses, it remains a challenge in the ongoing development for an effective vaccine for COVID-19.
Keywords: COVID-19; MERS; SARS; immunity; immunoglobulin; convalescent plasma